"I Know Who I Am and What I Represent": Asserting Indigenous Labrador Identity. (4th May 2019) - Hallett, Vicki S.
Abstract: The following essay is an interdisciplinary engagement with the life writing of Doris Saunders, founding editor of Them Days magazine. Using postcolonial and decolonial life writing theories, it argues that Saunders asserted an Indigenous Labrador identity through her personal essays, speeches and letters by negotiating boundaries of colonial ideologies present in the settler state and a local Indigenous organization.